Quantized control settings based tuning of a heaving wave energy converter in irregular seas. Issue 12 (25th September 2016) - Mistikoglu, Selcuk; Yavuz, Hakan
ABSTRACT: The increasing awareness of environmental issues attracts more attention on environmentally friendly energy sources. This leads to increasing research on effective use of renewable energy sources. Among them, wave energy offers a high potential. The wave energy converter systems used for transforming the wave energy into electrical energy have been a main research topic for decades. However, only a few of these systems has been successfully implemented. There seems to be some technical problems one of which is on their control applications. It has been reported that by means of appropriate control implementation, the performance of the wave energy converter system could be improved considerably. In literature, many different control techniques are reported. They appear to be weak due to implementation related restrictions. The present study proposes a novel control technique that is far more practical based on quantization of control settings. Various quantization levels and their effect on system power capture performance are studied. The technique assumes use of realistic off-the-shelf components with realistic features. The proposed method utilizes time-series-analysis technique with online parameter estimation feature. This new method does not require any knowledge of previous or future states of any of the system or sea state parameters, but only the currently available and measurable ones. The approach of the new control technique sets it apart from most of the previously reported ones. Therefore, the proposed technique is not only very much practical but also very much useful in improvement of the system power performance relative to passive techniques.